Apelin, C-reactive protein, and serum protein correlation with blood pressure ‒ a biomarker analysis - Mutaeb, Zahraa Ahmed; Ramadhan, Usama H.; Jasim, Ekhlas Qanber (Rzeszów University Press, 2025)
Introduction and aim. Hypertension is a major global health burden and a leading cause of cardiovascular disease and premature death. This study aimed to evaluate the association between serum apelin, inflammatory markers, and protein metabolism parameters in hypertensive patients compared to normotensive controls. This study uniquely explores the interplay between inflammatory and protein metabolism biomarkers using advanced multivariate models in hypertensive adults, a combination not previously examined in this population Material and methods. Two hundred adults aged 35–65 years were divided into hypertensive (n=100) and normotensive (n=100) groups. Serum apelin and C-reactive protein (CRP) levels were measured using enzyme-linked immunosorbent assay, while albumin and total protein were assessed via spectrophotometry. Statistical analyses included t-tests, multiple regression, structural equation modeling (SEM), and Cox regression. Results. Hypertensive patients had significantly higher blood pressure (p<0.001), CRP (7.52±4.21 vs. 1.35±0.51 mg/L; p<0.001), globulin (3.4±1.0 vs. 1.8±0.9 g/dL; p<0.001), and total protein, but lower apelin (2386.2±401.7 vs. 2873.4±572.8 pg/mL; p<0.001) and albumin levels. SEM revealed a direct association between CRP and systolic blood pressure (β=0.45, p<0.001), and a negative association between apelin and systolic pressure (β=−0.20, p=0.03). CRP (HR=1.75, p=0.005) and systolic BP (HR=1.52, p<0.001) were independent predictors of cardiovascular events. Conclusion. The findings suggest that systemic inflammation and dysregulation of serum protein metabolism are significantly associated with hypertension and cardiovascular risk. Apelin may play a protective role by mitigating the impact of inflammation on blood pressure.
All human contact methods described in this study were approved by the University of Basrah’s Human and Animal Ethics Committee in Iraq (No. 2024/112).
Keywords: adipokines; albumin; apelin; blood pressure; C-reactive protein